Compassionate, collective or transformational nursing leadership to ensure fundamentals of care are achieved: A new challenge or non‐sequitur?. (17th March 2022) - Pattison, Natalie; Corser, Rachael
Abstract: Aims: This discursive paper draws on three key leadership theories with the aim of outlining how styles of leadership impact the provision of fundamentals of care. Design: Discussion paper. Data sources: key leadership theories, leadership and fundamentals of care literature. Implications for Nursing: The conceptualization of fundamentals of care is viewed through the lens of nursing leadership, and collective, compassionate and transformational leadership theory. The cognitive dissonance that nursing leaders encounter when trying to reconcile organizational, patient and nurses' needs is considered, and the pressure to deliver high‐quality fundamentals of care presents a challenge to nurse leaders. Conclusion: Leaders must align nursing and patient outcome data to drive forward and prioritize fundamental care. Focusing on key elements of relational leadership styles will ensure a workforce fit to provide fundamental care, which in the current climate must be an organizational and global nursing priority. Impact: This discussion attempts to draw together overlapping leadership theories, emphasizes the importance of relational leadership in ensuring the provision of the fundamentals of care and acknowledged the impact of the COVID‐19 pandemic on nurses and nursing care, with leadership implications outlined, such as a need for role‐modelling, understanding shared values and giving nurses a voice. It will have an impact on nurse leaders, but also on those nurses providing direct care by issuing a challenge for them to confront their own nurse leaders, and to ask that they better resolve competing needs of both the nursing workforce and patients.